KARAKTERISTIK SENI LUKIS KARYA SOEGENG TOEKIO - Isnanta, Satriana Didiek (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2017)
The study entitled "Characteristics Of Soegeng Toekio's Paintings". The focus of this research is to find the character of Soegeng Toekio’s paintings in order to know the weaknesses and shortcomings Soegeng Toekio’s works together. The first step taken is collecting data from all three sources of information required by the holistic art criticism, namely, the creation of works Soegeng Toekio’s backgrounds as genetic information, Soegeng Toekio’s paintings as objective information and gazerer comments as affective information. Once the source of the data collected and analyzed using analysis of interaction (the Information sources of genetic and affective) and interpretive analysis of sources of objective information. After all the data is analyzed and then synthesized and conclusions drawn with regard to the characteristics of Soegeng Toekio’s painting.Results from this study is the character of Soegeng Toekio’s painting are illustrative figurative decorative style, the paintings with decorative styles, with strength in typical comical figure with forms like wayang beber. Illustrates the tradition of events identified from the human figure clothes which are then contrasted/ contrasted with popular contemporary colors. Keywords: Soegeng Toekio, characteristics, painting, art criticism, holistic